Two Factor Authentication Using Token and TAC - Mohamed Ismail, NurulSalimah Binti; Mohd Husny, Herny Ramadhani (Journal of Computing Technologies and Creative Content, 2019)
Abstract— Nowadays single authentication is not secure anymore and easy to be hacked. the widely used of authentication to secure the account from unauthorized parties has been make two-factor authentication being develop to make a strong authentication. This paper presents the development of two-factor authentication using USB Token and TAC that receive through Email. The process including developing requirement model, prototype construction and usability testing. The objective of this study are to develop strong authentication that used combination of USB Token and TAC as a two-factor authentication. The Prototyping Model methodology is used as the process flow for this project